(untitled) (American Journal of Interdisciplinary Research and Development, 2023)
The article is about the typology of jewelry found in stone, especially late Paleolithic, Mesolithic and Neolithic sites and settlements of Central Asia. It provides an analysis of the types of jewelry made of stone, organic materials, etc., from all phases of the Middle Asian Stone Age. Also, brief information about the making of jewelry and their cultural-ideological significance is given. This article focuses on the comparison of archaeological and ethnographic data on the main types of ornaments and their functions, which are considered an integral part of the spiritual and ideological life of the Central Asian Stone Age communities. It is emphasized that it is a primary source about the aesthetic and ideological and religious views of the types of jewelry of the Central Asian Stone Age communities.